MERCURY CHLORIDE (HgCl2) EXPOSURE CHANGES THE HISTOPATHOLOGICAL FIGURE OF EYE AND BRAIN OF TILAPIA FISH (Oreochromis mossambicus) - Dwinna Aliza; Nazaruddin Nazaruddin; Aya Sofia Abda; Annisa Asri (SEAMEO BIOTROP, 2022)
Mercury pollution brings harmful effects to aquatic animals, the environment and eventually to human health. Mercury accumulates in the liver, kidney, eye lens and brain of fish, resulting in organ damage. This study aimed to determine the effect of HgCl2 exposure on anatomical pathology and histopathology of tilapia fish eye and brain. A total of 36 male tilapia fish were allotted into 4 treatment groups with 3 replications. Fish were exposed to 0.00, 0.25, 0.50, and 0.75 ppm of HgCl2 for 10, 20, and 30 days. Subsequently, the anatomical pathology was observed followed by histopathological examination. Anatomical pathology examination of fish eye on day 30 showed white membrane on the eye lens surface, pupil diminution, and sunken eyes. The brain demonstrated hemorrhage, necrosis, discolorations, and granulated area. The retina showed necrosis, retina pigmentation flexiform layer widened, and cone cell atrophy. Brain depicted structural and cellular damage such as degeneration necrosis and vacuolation. HgCl2 exposure changes the anatomical pathology and histopathology of tilapia fish eye and brain.